Practical ship design - Watson, David G. M. (Amsterdam ; New York : Elsevier, 1998)
The ever-growing demand for commercial activities at sea has meant that ships are rapidly developing and that the rules governing their construction and operation are changing. Practical Ship Design records these changes, their outcomes and the reasoning behind them. It deals with every aspect of ship design and handles a wide range of both merchant ships and naval ships with authority. It provides coverage of cargo ships and passenger ships, tugs, dredgers and other service craft. It also includes concept design, detail design, structural design, hydrodynamics design, the effect of regulations, the preparation of specifications and matters of costs and economics. Drawing on the author's extensive practical experience, Practical Ship Design is likely to interest everybody involved in the design, construction, repair and operation of ships. Students and the most experienced professionals will all benefit from the book's vast store of design data and its conclusions and recommendations.
Chapter headings and selected papers: Foreword. Preface. Introduction, Methods and Data. Design calculation methods. Ship design data. Setting Design Requirements. Merchant ship requirements and transportation studies. Staff requirements for warship and naval auxiliary vessels. The Design Equations. The weight equations. The volume equations. Weight-Based Designs. Outfit weight calculations. Lightship centres of gravity. Volume, Area and Dimension-Based Designs. Estimating the required volume. Crew numbers. Powering I. An introduction to powering. Resistance and ship model correlation. Powering II. Propulsive efficiency. Design Of Lines. The bow and stern. Seakeeping and manoeuvrability. Machinery Selection. Introduction and criteria for choosing the main engine. Structural Design. Factors influencing structural design. Special strength considerations for particular ship types. Freeboard and Subdivision. Deterministic rules for passenger ships. Probabilistic rules for cargo ships. Stability and Trim & mdash; General. Damaged stability standards for reduced freeboard. Constant displacement and added weight. Other Statutory Rules. MARPOL & mdash; marine pollution rules. Tonnage rules. Special Factors Influencing Warship Design. Warship roles. Combat systems. The General Arrangement. Factors influencing the general arrangement. Arranging accommodation. General Arrangement of Some Ship Types. A specialist ship & mdash; R.D.N. fishery inspection ship "Thetis". Guidance on designs from significant ships. Specification and Tender Package. Specification principles. Things to avoid when writing, or accepting a specification. Cost Estimating. Cost and price. Structural costs. Operational Economics. Economic criteria. Operating costs. Conversions. Modifications to increase deadweight or capacity. Bibliography. Subject index.
Includes bibliographical references and index.
Keywords: Naval architecture; Electronic books